Deoxyribonucleic Acid Methylation in Systemic Lupus Erythematosus: Implications for Future Clinical Practice - Weeding, Emma; Sawalha, Amr H. (Frontiers in Immunology, 2018)
Differential DNA methylation has emerged as a critical feature of systemic lupus erythematosus (SLE). Genome-wide DNA methylation studies have revealed methylation patterns characteristic of SLE—in particular, robust hypomethylation of interferon-regulated genes is a prominent finding in all cells of the immune system studied to date. These patterns reliably distinguish individuals with SLE from healthy controls and from individuals with other autoimmune diseases. For example, hypomethylation within IFI44L is both highly sensitive and highly specific for SLE, superior to currently available biomarkers. Furthermore, methylation status of other genetic loci has been associated with clinically relevant features of SLE including disease severity and organ-specific manifestations. Finally, DNA methylation studies have provided important insights into the pathophysiology of SLE. Most recently, there is a growing body of evidence that the transcription factor EZH2 plays an important role in triggering SLE disease activity via epigenetic mechanisms, and that EZH2 blockade may be a future treatment option in SLE. In this short review, we discuss the DNA methylation patterns associated with SLE, their relationship to clinically significant features of SLE, and their implications in the development of novel diagnostic and therapeutic approaches to this complex disease.